The Role of Inundation Types of Tidal Swampland on the Chemical Properties of Potentially Acid Sulphate Soils under Fertilizer and Lime Application - Arifin Fahmi; Muhammad Alwi; Dedi Nursyamsi (UNIVERSITY OF LAMPUNG, 2018)
Generally, fertilizer application increases soil fertility, on the other hand fertilizer application leads to the alteration of soil chemical balances in which the magnitude of changes is determined by soil properties. The research aimed to study the soil chemical properties of potentially acid sulphate soils (PASS) originally from two types of tidal swampland as influenced by the application fertilizers and lime. A pot experiment was carried out in a glasshouse. Soil samples were taken from PASS originated from two types of tidal swampland, i.e. PASS in type B tidal swampland (PASS-B) and PASS in type C tidal swampland (PASS-C). The experiment was arranged in single factor of completely randomized design, consisting of six levels of urea, SP-36, and KCl fertilizers and lime that were determined based on Decision Support System software (DSS). Soil pH, total nitrogen (N), available phosphorus (P), exchangeable potassium (K) and iron (Fe) were measured periodically every four weeks, soil redox potential (Eh) was measured every week, leaf color index was measured every two weeks. The dynamics of soil pH, concentration of P, K, Fe and N of PASS were influenced by the application of fertilizer rates and lime, although, the magnitude of their changes were influenced by inundation type of tidal swampland. These facts were mainly associated with the presence of Fe mineral in both soils, the different concentration of Fe2+ in PASS-B and PASS-C may be related to land hydrological condition of type B tidal swampland that is frequently flooded as origin of PASS-B.